Influence of parenthood on school violence: a systematic review - Tapullima-Mori, Calixto (2023)
School violence has been a widely studied subject as well as its factors or predictors; In this sense, the objective of this study was to analyze how parenting influences school violence. The study included a systematic review governed by the PRISMA and Cochrane manuals, the explored databases were SCOPUS (346), PROQUEST (97), SCIELO (7) and PUBMED (661), for the search the descriptors and Boolean operators were used. (AND and OR); the preliminary extraction yielded 1111 articles and after applying the selection criteria, 22 were systematized. In this sense, the main results show that parenthood represents a determining factor for the development of adolescent behavior in the face of certain circumstances that arise in the educational context; For this reason, it is considered fundamental that parents assume their roles positively and educate their children with respect and love, avoiding at all times resorting to punishments that affect the physical and emotional state, especially those who are in adolescence due to because they present various psychological changes and have less capacity to regulate their emotions and/or feelings. In conclusion, the absence of positive parenting in the family environment has a negative impact on the behavior of adolescents, which leads to the practice of violent attitudes and psychosocial problems.